Financial Derivatives, Financial Leverage, Intangible Assets, and Transfer Pricing Aggressiveness: Evidence from Indonesian Companies - Firmansyah, Amrie; Yunidar, Artikayara (Jurnal Dinamika Akuntansi dan Bisnis, 2020)
This study aim to examine the effect of financial derivatives, financial leverage, and intangible assets on transfer pricing aggressiveness. The samples are nonfinancial companies listed on the Indonesia Stock Exchange (IDX) from 2012 to 2016. Using purposive sampling method, 44 selected companies data were selected (220 year-firm observations). The data was analyzed using multiple regression analysis with panel data. The results suggest that financial derivatives, financial leverage, and intangible assets have a positive effect on transfer pricing aggressiveness. This study shows that financial derivatives in Indonesia, both with the aim of hedging and with speculative purposes, have the same nature and are closely related to profit shifting conducted by the companies.